THE RELATION OF PARENT’S ROLE WITH INDEPENDENCE PERSONAL HYGIENE OF PRESCHOOLCHILDREN (AGES 4-6 YEARS) (correlationstudiesinTK Dharma Wanita Padas district of Bungkal Ponorogo) - Muhammad Zainul Mushthofa; Sri Sayekti; Inayatur Rosyidah; Marxis Udaya (Jurnal Keperawatan, 2015)
Self-reliance were studied by pre school children depend on the readiness and maturity, especially given theopportunity to learn the guidance of parents. The role of parents as caregivers, the response of the environment,it is necessary child as a reinforcement for each behavior. The purposes of this research is to know, analyzerelation of parent’s role with independence personal hygiene of pre-school children (ages 4-6 years) inTKDharma Wanita Padas district of Bungkal Ponorogo.This research design was analytic cross sectional with population of all parents who have pre-school childrenage 4-6 years in TK Dharma Wanita Padas district of BungkalPonorogo with total 32 people and the sampleswas a number of 32 people with total sampling technique. The variables in this research consist of 2 variablesthose were independent variable was parents’ role and dependent variable was independence personal hygieneof pre-school children (ages 4-6 years), while data collecting used a quetionnaire, data analysis, editing,coding, scoring, tabulating. Statistic test used chi square test.The result of this research obtained that mostly respondents were 18 the parent’s role were positive (56,3%) andmostly respondents were 18 people were indepence personal hygiene of pre-school children was good (56.3%).The relation of parents role with independence personal higiene pre school children there are 13 respondents(40,6%), while based on the test results chi square test with SPSS obtained (= 0,008) so H1 accepted thatmeans there is relation of parent’s role with indepencepersonal hygiene of pre-school children (age 4-6 years)in TK Dharma Wanita Padas district of Bungkal Ponorogo.